2022
DOI: 10.1001/jamanetworkopen.2022.7722
|View full text |Cite
|
Sign up to set email alerts
|

Association of Immune Checkpoint Inhibitors With Neurologic Adverse Events

Abstract: Key Points Question What is the association of the use of checkpoint inhibitors with the risk of neurological adverse events? Findings In this meta-analysis of 39 trials evaluating the use of checkpoint inhibitors to treat various malignant neoplasms, the risk of neurological adverse events was lower when compared with chemotherapy. However, the risk of neurologic adverse events was higher with checkpoint inhibitors compared with placebo. Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…Melanoma can be divided into superficial spreading melanoma, lentigo malignant melanoma, and nodular melanoma. Superficial spreading melanoma accounts for 70%, lentigo malignant melanoma 4-15% and nodular melanoma 5% of all the melanomas [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanoma can be divided into superficial spreading melanoma, lentigo malignant melanoma, and nodular melanoma. Superficial spreading melanoma accounts for 70%, lentigo malignant melanoma 4-15% and nodular melanoma 5% of all the melanomas [10].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of melanoma has the advantage of the cutaneous location, which leads to early detection through non-invasive approaches. However, the gold standard for the diagnosis is pathological review via biopsy [10].…”
Section: Discussionmentioning
confidence: 99%
“…[4] It was reported that patients who developed MG had an early onset during the treatment course with rapid progression, similar to our patient's clinical course. A recent systematic review and meta-analysis of the association of ICIs with neurologic adverse events suggested that the overall risk of neurologic adverse events (NAEs), peripheral neuropathy, and dysgeusia was lower with the use of ICIs when compared with chemotherapy, but higher when compared with placebo [5]. Despite the rarity of adverse events, prompt identification is advised to provide respiratory support either through noninvasive positive pressure ventilation or mechanical ventilation to prevent patients from experiencing acute respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…Dysgeusia has been reported as an irAE in 16 randomized controlled trials, with a pooled incidence of 4.9% [ 46 ]. A recent single center retrospective review estimated the incidence to be 3.6% [ 14 ].…”
Section: Other Orofacial Iraesmentioning
confidence: 99%